Many-Body Effects on Electronic Properties and Optical Response of Single-Layer Penta-NiN2 for Infrared Optoelectronics - Marinho, Enesio [UNESP]; Villegas, Cesar E. P.; Venezuela, Pedro; Rocha, Alexandre R. [UNESP] (American Chemical Society (ACS), 2024)
We present a comprehensive first-principles study on the optoelectronic properties of the single-layer nickel diazenide (penta-NiN2), a pentagon-based 2D semiconductor with ideal Cairo tessellation, whose bulk counterpart has been recently synthesized. To address its quasiparticle band structure and excitonic effects on its optical absorption spectrum, we carry out ab initio calculations based on many-body perturbation theory within the GW-Bethe-Salpeter equation (BSE) framework. Our results reveal a quasiparticle band gap of 1.05 eV by employing the eigenvalue self-consistent GW approach, corroborating its potential in optoelectronics. The band gap exhibits an anomalous negative dependence on temperature, verified through the band gap pressure coefficient. Acoustic phonon-limited scattering analyses indicate an ultrahigh hole mobility of ∼87 × 104 cm2 V-1 s-1 along the [010] direction. The most prominent absorption peak of monolayer penta-NiN2 is associated with resonant excitons, corresponding to transitions from the valence band maximum to conduction band minimum + 2, which is explained by analyzing the state symmetry of the band edges. Hence, this pentagonal 2D semiconductor exhibits compelling and promising properties deserving deeper exploration in infrared optoelectronics and high-speed devices.
Keywords: Cairo tiling; excitons; GW-BSE formalism; infrared optoelectronics; pentagonal 2D semiconductor